A Qualitative Assessment of the Living Donor Navigator Program to Identify Core Competencies and Promising Practices for Implementation. (March 2020) - Reed, Rhiannon D.; Hites, Lisle; Mustian, Margaux N.; Shelton, Brittany A.; Hendricks, Daagye; Berry, Beverly; MacLennan, Paul A.; Blackburn, Justin; Wingate, Martha S.; Yates, Clayton; Hannon, Lonnie; Kilgore, Meredith L.; et al.
Introduction: The best strategy to increase awareness of and access to living kidney donation remains unknown. To build upon the existing strategies, we developed the Living Donor Navigator program, combining advocacy training of patient advocates with enhanced health-care systems training of patient navigators to address potential living donor concerns during the evaluation process. Herein, we describe a systematic assessment of the delivery and content of the program through focus group discussion. Methods: We conducted focus groups with 9 advocate participants in the Living Donor Navigator program to identify knowledge, skills, and abilities needed for both advocates and navigators. We focused on 2 organizational levels: (1) the participant level or the advocacy training of the advocates and (2) the programmatic level or the support role provided by the navigators and administration of the program. Findings: From 4 common themes (communication, education, support, and commitment), we identified several core competencies and promising practices, at both the participant and programmatic levels. These themes highlighted the potential for several improvements of program content and delivery, the importance of cultural sensitivity among the Living Donor navigators, and the opportunity for informal caregiver support and accountability provided by the program. Discussion: These competencies and promising practices represent actionable strategies for content refinement, optimal training of advocates, and engagement of potential living donors through the Living Donor Navigator program. These findings may also assist with program implementation at other transplant centers in the future.